Pr-magnetism in the quasi-skutterudite compound PrFe2Al8. (28th July 2017) - Nair, Harikrishnan S; Ogunbunmi, Michael O; Kumar, C M N; Adroja, D T; Manuel, P; Fortes, D; Taylor, J; Strydom, A M
Abstract: The intermetallic compound PrFe2 Al8 that possesses a three-dimensional network structure of Al polyhedra centered at the transition metal element Fe and the rare earth Pr is investigated through neutron powder diffraction and inelastic neutron scattering in order to elucidate the magnetic ground state of Pr and Fe and the crystal field effects of Pr. Our neutron diffraction study confirms long-range magnetic order of Pr below T N = 4.5 K in this compound. Subsequent magnetic structure estimation reveals a magnetic propagation vector k = ( 1 2 0 1 2 ) with a magnetic moment value of 2.5 μ B /Pr along the orthorhombic c -axis and evidence the lack of ordering in the Fe sublattice. The inelastic neutron scattering study reveals one crystalline electric field excitation near 19 meV at 5 K in PrFe2 Al8 . The energy-integrated intensity of the 19 meV excitation as a function of | Q | ( A ˚ − 1 ) follows the square of the magnetic form factor of P r 3 + thereby confirming that the inelastic excitation belongs to the Pr sublattice. The second sum rule applied to the dynamic structure factor indicates only 1.6(2) μ B evolving at the 19 meV peak compared to the 3.58 μ B for free P r 3 +, indicating that the crystal field ground state is magnetic and the missing moment is associated with the resolution limited quasi-elastic line. The magnetic order occurring in Pr in PrFe2 Al8 is counter-intuitive to the symmetry-allowed crystal field level scheme, hence, is suggestive of exchange-mediated mechanisms of ordering stemming from the magnetic ground state of the crystal field levels.